Challenges in Clinico-Genetic Correlations in Parkinson’s disease (PD): The Role of Copy Number Variants (CNV) - Gatto, Emilia Mabel (2021)
Parkinson’s disease (PD) represents the second most common neurodegenerative disease and remains incurable. Mutations in multiple genes have been linked to monogenic PD (gPD); these monogenic forms, however, represent a small number of cases while in most instances PD appears as idiopathic (iPD). These findings raise the question of whether genetic and idiopathic parkinsonisms constitute the same disease. Nevertheless, monogenic-PD phenotypes and iPD both fulfill MDS criteria for PD, and show evidence of alpha-synuclein aggregates in both conditions. Distinct genetic loci in rare Mendelian forms have been identified as causal mutations, others as possible disease-causing genes, and genome-wide association studies have reported several risk loci, many of them located in the genes associated with the dominant mutations. Not only single-nucleotide polymorphisms (SNPs), but other kinds of DNA molecular defects as well have been spotted as significant disease-causing mutations, including large chromosomal structural rearrangements and copy number variations (CNVs). As their size varies, and detection methodologies have different sensitivity and resolution, CNVs pose a special challenge in genetic studies, and there currently is a debate on the pathogenetic or susceptibility impact of specific CNVs on PD. In this review, through multiple instances of experimental evidence, we analyze the impact on histopathology of the different mutational mechanisms involved in the genesis and etiology of PD. We believe that increasing our knowledge about the changes and implications at tissue level produced by each of those mechanisms will allow to develop much more suitable and personalized potential therapeutic strategies, biomarker identification, as well as disease modeling, agreeing with the precision medicine concept.